BioDeepTime: A database of biodiversity time series for modern and fossil assemblages - Smith, Jansen; Rillo, Marina C.; Kocsis, Ádám; Dornelas, Maria; Fastovich, David; Huang, Huai Hsuan M.; Jonkers, Lukas; Kießling, Wolfgang; Li, Qijian; Liow, Lee Hsiang; Margulis-Ohnuma, Miranda; Meyers, Stephen; et al. (Global Ecology and Biogeography, 2023)
Motivation: We have little understanding of how communities respond to varying magnitudes and rates of environmental perturbations across temporal scales. BioDeepTime harmonizes assemblage time series of presence and abundance data to help facilitate investigations of community dynamics across timescales and the response of communities to natural and anthropogenic stressors. BioDeepTime includes time series of terrestrial and aquatic assemblages of varying spatial and temporal grain and extent from the present-day to millions of years ago. Main Types of Variables Included: BioDeepTime currently contains 7,437,847 taxon records from 10,062 assemblage time series, each with a minimum of 10 time steps. Age constraints, sampling method, environment and taxonomic scope are provided for each time series. Spatial Location and Grain: The database includes 8752 unique sampling locations from freshwater, marine and terrestrial ecosystems. Spatial grain represented by individual samples varies from quadrats on the order of several cm2 to grid cells of 100 km2. Time Period and Grain: BioDeepTime in aggregate currently spans the last 451 million years, with the 10,062 modern and fossil assemblage time series ranging in extent from years to millions of years. The median extent of modern time series is 18.7 years and for fossil series is 54,872 years. Temporal grain, the time encompassed by individual samples, ranges from days to tens of thousands of years. Major Taxa and Level of Measurement: The database contains information on 28,777 unique taxa with 4,769,789 records at the species level and another 271,218 records known to the genus level, including time series of benthic and planktonic foraminifera, coccolithophores, diatoms, ostracods, plants (pollen), radiolarians and other invertebrates and vertebrates. There are to date 7012 modern and 3050 fossil time series in BioDeepTime. Software Format: SQLite, Comma-separated values.
CRIS-Team Scopus Importer:2023-08-04
Keywords: deep-time; global; palaeobiology; species richness; temporal; timescale; turnover